LEXICAL STYLISTIC DEVICES: METAPHOR, METONYMY, IRONY, AND EPITHET - Axmatxonova Mubina; Abdulazizova Sevara (TADQIQOTLAR, 2025)
This article explores four key lexical stylistic devices—metaphor, metonymy, irony, and epithet—which are essential tools for enhancing expressive power in English language and literature. Each device is explained with definitions and examples to help readers understand how they add emotional and imaginative depth to communication.